Effects of Water Deficit on Growth and Productivity in Tomato Crops Irrigated with Water Treated with Very Low-Frequency Electromagnetic Resonance Fields - Putti, Fernando Ferrari [UNESP]; de Queiroz Barcelos, Jéssica Pigatto [UNESP]; Goes, Bruno Cesar; Alves, Renata Fernandes [UNESP]; Neto, Mário Mollo [UNESP]; da Silva, Alexsandro Oliveira; Filho, Luís Roberto Almeida Gabriel [UNESP]; Zanetti, Willian Aparecido Leotti [UNESP]; de Souza, Angela Vacaro [UNESP] (MDPI, 2023)
The tomato crop is very sensitive to stress conditions. A water deficit is defined as when precipitation is less than the evapotranspiration (ETc) of the crop in a given period, and in this scenario of climate change, it is identified as responsible for global productivity losses. The use of potential technologies for better irrigation management, such as electromagnetically treated water, remains controversial. Thus, the objective of the present work was to investigate the effects of very low-frequency electromagnetic resonance field treatment on water for tomato crops submitted to different irrigation rates. For this, an experiment was carried out under controlled conditions with different types of water: electromagnetically treated water (WTVLF) and untreated water (UNW), as well as four water replacement rates: 40, 60, 80, and 100% ETc. The electromagnetic treatment of the water was carried out using the commercial equipment AQUA4D®. The experiment was carried out in pots with five replications per treatment. Lower activity of SOD, POD, CAT, and APX enzymes was observed in plants irrigated with water treated with very low-frequency electromagnetic resonance fields (WTVLF), indicating less oxidative stress caused by water deficit. Water deficit reduced chlorophyll content, but the effects were less harmful with WTVLF water. The water deficit resulted in less accumulation of dry matter and less productivity in a linear relationship. However, plants irrigated with WTVLF showed increments of about 20% in dry matter accumulation and 20% in fruit production concerning plants irrigated with untreated water, independent of the irrigation rates. We can conclude that irrigation with WTVLF can be a solution to reduce the damage caused by water deficits and increase the productivity of tomato crops.
Keywords: drought stress; EROs; Solanum lycopersicumL